Despatch from Sir R. Morier, inclosing the reply of the Russian government in regard to the seizures of British sealing vessels by Russian cruizers in the North Pacific Ocean [electronic resource] : presented to both Houses of Parliament by Command of Her Majesty, June 1893. - Morier, R. (Robert), Sir, 1826-1893. (London : Harrison, 1893)
Original issued in series: [Command papers / Great Britain. Parliament] Cd. 7029. At head of title: Russia. No. 3 (1893). Electronic reproduction. Mode of access: Internet. 44